2004
DOI: 10.1093/jjco/hyh001
|View full text |Cite
|
Sign up to set email alerts
|

Superior Anti-tumor Efficacy of Bicalutamide 80 mg in Combination with a Luteinizing Hormone-releasing Hormone (LHRH) Agonist Versus LHRH Agonist Monotherapy as First-line Treatment for Advanced Prostate Cancer: Interim Results of a Randomized Study in Japanese Patients

Abstract: In Japanese patients with advanced prostate cancer, first-line treatment with bicalutamide 80 mg in combination with an LHRH agonist is superior to LHRH agonist monotherapy in terms of the antitumor response at 12 weeks, and also time to treatment failure and progression, and does not compromise treatment safety. The study is ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 12 publications
2
71
0
Order By: Relevance
“…[27][28][29][30] Furthermore, an established 5-R inhibitor such as finasteride can reduce intraprostatic levels of DHT. 31 Finasteride prevents or delays the appearance of prostate cancer, 32 although it can increase the detection of high-grade cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] Furthermore, an established 5-R inhibitor such as finasteride can reduce intraprostatic levels of DHT. 31 Finasteride prevents or delays the appearance of prostate cancer, 32 although it can increase the detection of high-grade cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have shown better outcomes in patients treated with CAB compared with LHRH agonist monotherapy. [28][29][30] However, a metaanalysis and randomized placebo-controlled clinical trial have revealed that the difference between LHRH agonist and CAB was only of a few percentage or nothing. 31,32 Therefore, the initial treatment strategy within the present step-up for hormonal therapy may be reasonable in clinical settings.…”
Section: 9%mentioning
confidence: 99%
“…Later on, the guidelines have been revised to clearly recommend 'consideration of MAB using bicalutamide' on the basis of one randomized clinical trial and one analytical research study [51][52][53]. The data quoted for the 2006 ASCO guidelines are results of interim analysis [53] (median follow-up of 66 weeks) of a multicenter, randomized, placebocontrolled phase III study comparing MAB group using bicalutamide and GnRH-A alone group for 205 Japanese patients with untreated advanced prostate cancer.…”
Section: A Combined Androgen Blockadementioning
confidence: 99%
“…The data quoted for the 2006 ASCO guidelines are results of interim analysis [53] (median follow-up of 66 weeks) of a multicenter, randomized, placebocontrolled phase III study comparing MAB group using bicalutamide and GnRH-A alone group for 205 Japanese patients with untreated advanced prostate cancer. Patients received an LHRH agonist and were randomly assigned to bicalutamide 80 mg orally once daily or placebo.…”
Section: A Combined Androgen Blockadementioning
confidence: 99%